Other Mediators At Age-Related Macular Degeneration - Turgut, Burak; Erdogan, Hakika; İlhan, Nevin; Erşan, İsmail (Gaziantep İslam Bilim ve Teknoloji Üniversitesi, 2022)
Objective Insome patients, even if anti-VEGF therapy is repeatedly administered at certain intervals, no response is obtained. Therefore, a search for new treatment methods has arisen. The aim of this study was to investigate the relevance of mediators such as Erythropoietin, Interleukin 17, and Angiotensin2,which are all involved in proliferation, apoptosis, oxidative stress, and inflammation in age-related macular degeneration. Metods EPO, IL-17, and Angiotensin 2 levels were evaluated by examining the blood samples of patients who did not have any systemic disease or chronic eye disease except Age-related Macular Degeneration (AMD). Results The patients were divided into 3 groups. Groups 1,2, and 3 were determined as the control group, dry type group, and neovascular type group respectively. For the purpose of this study, erythropoietin, interleukin 17, angiotensin2 were examined in the blood samples of patients. As a result of the analyses, a statistically significant difference was detected between the groups in terms of EPO, IL-17, and Angiotensin 2. Conclusion If the relationship between many factors related to age-related macular degeneration can be clearly defined, the perspective on treatment may change, especially in treatment-resistant patients.
Keywords: Clinical Sciences; Klinik Tıp Bilimleri